2018
DOI: 10.1002/jac5.1041
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' role in glycemic management in the inpatient setting: An opinion of the endocrine and metabolism practice and research network of the American College of Clinical Pharmacy

Abstract: The objective of this opinion paper was to identify and describe the role of pharmacists in ensuring safe and optimal management of patients with glycemic excursions in the inpatient setting. The role of the pharmacist includes involvement in admission medication history and reconciliation, formulary management of glucose‐lowering medications and devices, individual patient medication management, discharge transition of care, and interprofessional collaboration with other health care providers. Recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Pharmacists attached to various surgical services have provided consultation to anesthesiologists at the service and individual patient levels regarding local anesthetic systemic toxicity (LAST) and enhanced recovery analgesic/anesthetic pathways (in light of the recent move toward increased local anesthetic use to reduce opioid exposure) as well as evolving surgical techniques. Collaboration with surgeons has often focused on risk assessments and treatment recommendations for preoperative and pharmacokinetic-based antimicrobial optimization [ 157 ], VTE and PONV prophylaxis [ 144 , 147 ], postoperative pain management, POI mitigation, and electrolyte replacement and nutrition support, including glycemic control [ 158 ]. In one 20-month pre-/post-study in which clinical pharmacists were directly involved, pre-implementation colonic SSIs were reduced from 10% to 2%, VTE rate decreased from 0.6% to 0%, and postoperative readmission rate decreased from 4.8% to 1.3% [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists attached to various surgical services have provided consultation to anesthesiologists at the service and individual patient levels regarding local anesthetic systemic toxicity (LAST) and enhanced recovery analgesic/anesthetic pathways (in light of the recent move toward increased local anesthetic use to reduce opioid exposure) as well as evolving surgical techniques. Collaboration with surgeons has often focused on risk assessments and treatment recommendations for preoperative and pharmacokinetic-based antimicrobial optimization [ 157 ], VTE and PONV prophylaxis [ 144 , 147 ], postoperative pain management, POI mitigation, and electrolyte replacement and nutrition support, including glycemic control [ 158 ]. In one 20-month pre-/post-study in which clinical pharmacists were directly involved, pre-implementation colonic SSIs were reduced from 10% to 2%, VTE rate decreased from 0.6% to 0%, and postoperative readmission rate decreased from 4.8% to 1.3% [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…can affect blood glucose (BG) levels. Multiple studies of pharmacy-led inpatient hyperglycemic management have demonstrated success in improving patient outcomes [ 4 8 ]. However, most hospitals do not have a designated team ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…can affect blood glucose (BG) levels. Multiple studies of pharmacy-led inpatient hyperglycemic management have demonstrated success in improving patient outcomes [4][5][6][7][8]. However, most hospitals do not have a designated team (i.e., diabetes stewardship) to assess and adjust insulin regimens (e.g., sliding scale intensity, dose, etc.…”
Section: Introductionmentioning
confidence: 99%
“…can affect blood glucose (BG) levels. Multiple studies of pharmacy-led inpatient hyperglycemic management have demonstrated success in improving patient outcomes [4][5][6][7][8]. However, most hospitals do not have a designated team (i.e., diabetes stewardship) to assess and adjust insulin regimens (e.g., sliding scale intensity, dose, etc.…”
Section: Introductionmentioning
confidence: 99%